How well are Australian infants and children aged 4 to 5 years doing? (Social Policy Research Paper 36) - Hardy, P; Wake, M; Misson, S; Berthelsen, D; Sanson, A (My University, 2008)
This report presents an analysis of the data from the first wave of the Longitudinal Study of Australian Children (LSAC) to explore the wellbeing of 5,107 children in the infant cohort of the study and the 4,983 children, aged 4 to 5 years, in the child cohort. Wave 1 of LSAC includes measures of multiple aspects of children's early development. These developmental measures are summarised in the LSAC Outcome Index, a composite measure which includes an overall index as well as three separate domain scores, tapping physical development, social and emotional functioning, and learning and cognitive development. This report explores five specific aspects of infants' and children's experiences, exposures and environments in relation to their Outcome Index scores: key sociodemographic characteristics covering the child, mother, family and neighbourhood; non-parental care experiences; child health-prenatal and postnatal experiences and exposures; maternal physical and mental health; the early educational experiences of the child cohort in the home and out-of-home contexts. (FaHCSIA abstract)
Keywords: Child Development; Childhood and child development; Child Development; Childhood and child development